A novel missense SMPD1 gene mutation, T460P, and clinical findings in a patient with Niemann–Pick disease type B presenting to a lipid disorders clinic. (September 2014) - Grasko, Yael; Hooper, Amanda J; Burnett, John R; Watts, Gerald F
Niemann–Pick disease, type B (NPD-B; OMIM 607616) is an inborn error of metabolism where reduced concentrations of the enzyme acid sphingomyelinase (ASM; EC 3.1.4.12) lead to multisystem disease though with survival into adulthood. The natural history of NPD-B is one of progressive hypersplenism and gradual deterioration of pulmonary function. We describe a 46-year-old South African man of French Huguenot descent who presented to a lipid disorders clinic with mixed hyperlipidaemia. Clinical examination and imaging findings revealed the presence of massive hepatosplenomegaly, interstitial lung disease and subclinical atherosclerosis; there were no neurological or cognitive abnormalities. Laboratory testing showed thrombocytopaenia, increased liver transaminases and mild hyperbilirubinaemia. Lysosomal enzyme analysis showed markedly reduced ASM activity, suggestive of NPD. DNA sequence analysis of the SMPD1 gene revealed that he was a compound heterozygote for the previously reported c.1829_1831delGCC (ΔR608) mutation and a novel missense mutation c.1378A > C (p.T460P). In conclusion, we describe the clinical findings of a case of NPD-B with mixed hyperlipidaemia, compound heterozygous for the SMPD1 ΔR608 mutation and a novel mutation, T460P.